HUBUNGAN RELIGIUSITAS DAN IKLIM SEKOLAH TERHADAP PERILAKU MORAL SISWA SMA - Azis Ilham Saputra; Sri Lestari Sri Lestari; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study was to determine the relationship between religiosity and school climate on the moral behavior of high school students. The method used to determine the relationship between religiosity and school climate on the moral behavior of high school students in this study is quantitative. The data in this study were obtained by researchers through the questionnaire distribution method. Furthermore, based on the research results it is also known that the magnitude of the R-square value is 0.472, meaning that the magnitude of the influence of the variables of religiosity and school climate together on moral behavior is 47.2%. Based on the results of the study, it can be concluded that there is a relationship between religiosity and school climate on student moral behavior, then there is a relationship or influence between high school student religiosity. This research implies that the results of this study indicate that there is a relationship between religiosity and students' moral behavior. therefore it is necessary to have moral education through religiosity both at school and in the family environment. This is because a student has deep knowledge and understanding of religious teachings, and practices his religious teachings obediently, he will reject and be negative towards behaviors that violate the teachings of his religion.